Diabetes Mellitus and the risk of Primary open angle glaucoma - Lavaju, P; Shah, S; Sharma, S; Maskey, R (Nepalese Journal of Ophthalmology, 2017)
Background: Diabetes mellitus (DM) is one of the risk factors for Primary open angle glaucoma (POAG). Inclusion of DM as a risk factor for POAG is controversial. The objectives of the study were to investigate whether Type II (T2) DM is a risk factor for POAG and to determine central corneal thickness (CCT) in the subjects with T2DM and to examine the relationship between T2DM and intraocular pressure (IOP). Materials and methods: A comparative cross sectional study was conducted including 189 subjects of age > 40 years. In Group I, 113 patients diagnosed with T2DM and Group II, age and sex matched 76 subjects with POAG without DM was included. Detailed ocular examination, IOP, CCT and funduscopy evaluation was done. Results: Most of the patients were more than 60 years of age with mean age 58 ± 11 years. Male: female ratio was 1:1. POAG was seen in 27.4% of patients with T2DM. Mean IOP in T2DM was 14.67± 2.63mmHg and in non diabetic, 17.25±4.47 mmHg (p <0.00). In group I, mean CCT was 538.83± 22.7μm and in group II, 531.26 ± 20.9μm (p-0.126). There was no association between CCT and glaucoma (p=0.072, 95% CI: -0.76 –17.46). The study could not elicit an association of T2DM with glaucoma. Duration of T2DM did not affect an association between T2DM and glaucoma (p-0.757). Random blood sugar (p<0.001) and oral hypoglycemic drugs (p=0.030) showed an association with glaucoma. Conclusion: The study failed to show an association between T2DM and primary open angle glaucoma and CCT though an association seen with IOP. A larger prospective comparative study may be help in understanding this association.